2019
DOI: 10.1038/s41698-019-0096-z
|View full text |Cite
|
Sign up to set email alerts
|

A machine learning based delta-radiomics process for early prediction of treatment response of pancreatic cancer

Abstract: Changes of radiomic features over time in longitudinal images, delta radiomics, can potentially be used as a biomarker to predict treatment response. This study aims to develop a delta-radiomic process based on machine learning by (1) acquiring and registering longitudinal images, (2) segmenting and populating regions of interest (ROIs), (3) extracting radiomic features and calculating their changes (delta-radiomic features, DRFs), (4) reducing feature space and determining candidate DRFs showing treatment-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
114
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 135 publications
(116 citation statements)
references
References 35 publications
1
114
0
1
Order By: Relevance
“…Radiomics analysis has been associated with several clinical end points, several researchers showed that it has a potential to be developed into an imaging biomarker using different imaging modalities. We showed earlier that CT based radiomics has a potential in a variety of applications (11)(12)(13)(14)(15)(16)(17)(18)(19). Researchers also showed that it has promise using MR images for instance, Wibmer et al (33) and Vignti et al (34) showed the radiomics features as potential imaging biomarkers in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Radiomics analysis has been associated with several clinical end points, several researchers showed that it has a potential to be developed into an imaging biomarker using different imaging modalities. We showed earlier that CT based radiomics has a potential in a variety of applications (11)(12)(13)(14)(15)(16)(17)(18)(19). Researchers also showed that it has promise using MR images for instance, Wibmer et al (33) and Vignti et al (34) showed the radiomics features as potential imaging biomarkers in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Also, to reduce directional dependence of texture features, directionspecific matrices are summed and averaged to create a final global matrix. This resulted in 73 DRFs that could be used for deltaradiomic analysis (17)(18)(19). In this study, patients were divided into good-and poor-response groups based on their treatment responses.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations